The sequence of film as subjective technique in audiovisual psychotherapy - Rueda Cuenca, Olga (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2012)
The present work is a summary of a study based on applying the Sequence Technique in Cinema (TSC) as a subjective tool with clients of the Experimental Videotherapy Workshop, at “espaciointerno psicología” in Madrid. A descriptive methodology, of qualitative orientation, through an open participative observation has been used to elaborate this study. To be able to generate some subjective, narrative information with the power to clarify the experience of the participants, a retro and prospective review of the selected filmic material has been done. Hints for future investigations show themselves as being the conclusion of this study.
Keywords: Cinematherapy; videotherapy; media psychology; self concept; mental representation.